2020
DOI: 10.3389/fpsyt.2020.00573
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mental Illness Stigma on Psychiatric Emergencies

Abstract: Psychiatric emergencies are severe behavioral changes secondary to worsening mental illness. Such situations present a risk to the patient and other people, so they need immediate therapeutic intervention. They are associated with feelings of fear, anger, prejudice, and even exclusion. The attitudes of professionals and factors related to the workplace culture in health can help to perpetuate stereotypes and interfere with the quality of care. Stigma has undesirable consequences in patients with mental disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 67 publications
1
25
0
8
Order By: Relevance
“…53 Some solutions to physician suicide may involve enhancing social networks, workplace support, expanding telehealth and mental health support, as well as educational campaigns reduce stigma (e.g., only 71.4% of psychiatrists followed the prescribed treatment if diagnosed with schizophrenia, even though all of them reported that pharmacotherapy was important). 54, 55 The pandemic, while increasing social distancing, has expanded professional and even personal connections online (e.g., family video meetings) and has led members of some health care communities to regularly check on each other online to see how they are doing. Such measures can benefit physicians beyond the pandemic and ease feelings of social isolation, whether they are surrounded by other people or not.…”
Section: Covid-19 Considerationsmentioning
confidence: 99%
“…53 Some solutions to physician suicide may involve enhancing social networks, workplace support, expanding telehealth and mental health support, as well as educational campaigns reduce stigma (e.g., only 71.4% of psychiatrists followed the prescribed treatment if diagnosed with schizophrenia, even though all of them reported that pharmacotherapy was important). 54, 55 The pandemic, while increasing social distancing, has expanded professional and even personal connections online (e.g., family video meetings) and has led members of some health care communities to regularly check on each other online to see how they are doing. Such measures can benefit physicians beyond the pandemic and ease feelings of social isolation, whether they are surrounded by other people or not.…”
Section: Covid-19 Considerationsmentioning
confidence: 99%
“…Such diseases interfere with the patient's critical thinking abilities and in turn with adherence to disaster measures. In addition, these patients are very susceptible to stigma and neglect ( 14 ). Treatment should be prioritized for the guidance and use of antipsychotics.…”
Section: Approach To the Main Situationmentioning
confidence: 99%
“…Changes in a patient's behavior that put them or others at risk and that require immediate therapeutic intervention (in a matter of minutes or a few hours) to prevent harm are called psychiatric emergencies. The most prevalent emergency situations are severe self-neglect, self-harm, suicidal behavior, depressive or manic episodes, aggressive psychomotor agitation, severely impaired judgment, intoxication, or withdrawal from psychoactive substances ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another impact of stigma for sufferers is the refusal of individuals to form marital relationships and the poor quality of care for physical illnesses among people with psychiatric illnesses (Singh et al, 2016). There is no doubt that this stigma denigrates the mentally ill and the health professionals and networks that are formed to support them (da Silva et al, 2020). The main target of several countries in dealing with mental health is suicide prevention (Patel & Gonsalves, 2019).…”
Section: Introductionmentioning
confidence: 99%